PENGEMBANGAN PERANGKAT PEMBELAJARAN TOPIK BILANGAN DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK DI MADRASAH IBTIDAIYAH - Mara Samin Lubis (JURNAL TARBIYAH, 2016)
Preliminary studies revealed that there is a problem in mathematics education system in Madrasah Ibtidaiyah. As a result, the students’ mathematical skills are low, especially in the early grades. The studies showed that the availability of facilities and learning media is still lacking. In addition, the teachers still use the old learning patterns i.e., the dominance of learning activities, limited opportunities for students’ expression. The teaching methods have not been able to develop an understanding and interest of students in mathematics. The objective of the study is to develop learning tools on the topic of addition and subtraction of numeral through approach realistic mathematics education to improve learning outcome in Madrasah Ibtidaiyah. This study combines design research model of Plomp (2013) and design research of Gravemeijer and Cobb (2006). Research stages include preliminary research, development/prototyping phase and assessment. To develop the learning trajectory on the topic of addition and subtraction of numeral through approach realistic mathematics education used design research of Gravemeijer and Cobb (2006), which consists of three phases i.e., the preparing  for the experiment, conducting experiment and retrospective analysis. In the stages of prototype development conducted evaluation formative to investigate the validity and practicalities that includes self-evaluation, expert review, focus groups, one-to-one, small group, and field tests. The study used quantitative and qualitative approaches, which quantitative data collected through test. Whilst, qualitative data obtained through observation, interview and field notes. Findings of the study showed that (1) the learning tools assessed valid, practical and effective by experts, (2) The implementation of the learning tools in a class showed that the pupils become enthusiastic in learning, improving their creativity and interaction. Thus, the study explains that the learning tools of realistic mathematics education may be effective to be used in improving the effectiveness of learning mathematics at Madrasah Ibtidaiyah, especially in the early grades.